MENINGKATKAN KEMAMPUAN PENJUMLAHAN BILANGAN MELALUI MEDIA MESIN FUNGSI MANUAL BAGI ANAK TUNAGRAHITA RINGAN KELAS DII / C di SLB LIMAS PADANG - Fazila Suwedi, Zulmiyetri, Rahmatrisilvia (Jurnal Penelitian Pendidikan Khusus, 2013)
This research is motivated by problems that appear in the field, namely a mild mental retardation children class DII / C in SLB Limas Padang who have difficulty in doing the numbers sum to 20. Under these conditions, this study aims to demonstrate the use of the media machine manual functions in improving numbers sum to 20 for mild mental retardation children class DII / C in SLB Limas Padang. This research Single Subject Research approach to the design of the ABA. Results of this study indicate that the media machine manual functions can improve the ability of numbers sum to 20 for mild mental retardation children.